Positive electrode material and preparation method thereof
Through the preparation method of positive electrode materials doped with aluminum, zirconium, and niobium and coated with lithium phosphate, the problems of improving the rate performance and stability of high-nickel lithium cobalt oxide positive electrode materials under high current conditions were solved, and efficient lithium ion diffusion and charge transfer of the materials were achieved, thereby improving the safety and stability of the battery.
Patent Information
- Application Number
- CN202510762194.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-09
- Publication Date
- 2025-09-05
AI Technical Summary
The improvement of the rate performance of high-nickel lithium cobalt oxide positive electrode materials under high current conditions has encountered technical bottlenecks, and the cation mixing phenomenon and interfacial side reactions have led to a decrease in discharge capacity.
A nickel-cobalt precursor, lithium source, aluminum source, zirconium source and niobium source are mixed and sintered, then impregnated with lithium phosphate solution and mixed with single-walled carbon nanotubes. A continuous conductive-ion conductive composite layer is formed by doping with aluminum, zirconium and niobium and coating with lithium phosphate, thereby optimizing the lithium ion diffusion path and constructing a three-dimensional conductive network.
It improves the high-rate charge and discharge performance of high-nickel lithium cobalt oxide positive electrode materials, reduces the risk of resistance and thermal runaway, and improves the stability and safety of the materials.
Smart Images

Figure CN120600788A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of positive electrode materials, and in particular to a positive electrode material and a preparation method thereof. Background Art
[0002] With the booming global new energy vehicle and energy storage markets, power battery technologies with high energy density, high safety, and long cycle life have become a common focus of attention in both industry and academia. Among the numerous cathode material systems, lithium nickel cobalt manganese oxide (NCM) and lithium nickel cobalt aluminum oxide (NCA) firmly hold a dominant position in the market due to their excellent overall performance. In particular, through the high nickel content (Ni ≥ 80 wt%) technology route, these materials have achieved significant improvements in energy density, providing key support for breakthroughs in electric vehicle range.
[0003] High-nickel cobalt oxide (NCA) cathode materials have become one of the most promising research areas in the power battery field due to their exceptional energy density (greater than 270 mAh / g) and high operating voltage (approximately 3.7 V). However, practical applications of these materials still face significant challenges. Limited by their intrinsic physicochemical properties and complex interfacial dynamics, improving their rate performance (i.e., capacity retention at high currents) faces multiple technical bottlenecks.
[0004] Currently, a variety of effective methods have been developed to improve the rate performance and, consequently, the cycling stability of NCA materials, including single crystallization technology, element doping strategies, and surface coating modification. However, it is worth noting that while these optimization methods address these issues, they also inevitably introduce new challenges, namely, the exacerbation of cation mixing and the deterioration of interfacial side reactions, which can negatively impact the discharge capacity of the material. Summary of the Invention
[0005] Therefore, in order to solve the above problems, the present invention provides a positive electrode material and a preparation method thereof.
[0006] To this end, on the one hand, the present invention provides a method for preparing a positive electrode material, comprising the following steps: S1, mixing a nickel-cobalt precursor, a lithium source, an aluminum source, a zirconium source and a niobium source, and sintering to obtain a sintered material; S2, immersing the sintered material in a lithium phosphate solution by an impregnation method, separating the solid and the liquid, and annealing to obtain an intermediate; S3, mixing the intermediate and carbon nanotubes to obtain a mixture, and sintering the mixture to obtain a positive electrode material.
[0007] In some embodiments, the step of immersing the sinter in the lithium phosphate solution in step S2 includes immersing the sinter in the lithium phosphate solution under vacuum conditions for 20-40 minutes and then under normal pressure conditions for 1-3 hours.
[0008] Preferably, during the impregnation process, one burnt material is submerged in the lithium phosphate solution, and the height of the lithium phosphate solution is at least 2 cm higher than the height of the burnt material.
[0009] In some embodiments, the solid-liquid separation step in step S2 includes centrifugation and drying, the centrifugal speed is 2000-4000 rpm, the centrifugal time is 4-6 min, the drying temperature is 50-70° C., the drying time is 10-14 h, and the drying condition is vacuum.
[0010] In some embodiments, the method for preparing the lithium phosphate solution includes the following steps: adding phosphoric acid dropwise to a lithium hydroxide solution in the presence of an alcohol solvent, and controlling the pH of the reaction system to 8-9. By controlling the pH of the reaction system to 8-9, the formation of impurities such as Li2HPO4 is avoided.
[0011] In some embodiments, the concentration of lithium phosphate in the lithium phosphate solution is 0.05-0.2M, preferably 0.1M.
[0012] In some embodiments, the particle size of the nickel-cobalt precursor is 2-6 μm, preferably 2-4 μm.
[0013] In some embodiments, the specific surface area of the nickel-cobalt precursor is 5-10m 2 / g, tap density is 1-3g / cm 3 .
[0014] In some embodiments, in step S1, the step of mixing the nickel-cobalt precursor, the lithium source, the aluminum source, the zirconium source, and the niobium source includes mixing the intermediate and the single-walled carbon nanotubes at a speed of 800-1200 rpm for 1-3 minutes, then mixing at a speed of 1800-2200 rpm for 2-4 minutes, and finally mixing at a speed of 3000-4000 rpm for 12-18 minutes.
[0015] In some embodiments, the sintering conditions in step S1 include increasing the temperature to 400-600°C at a heating rate of 1-5°C / min and holding the temperature for 3-5 hours in an air or oxygen atmosphere, and then increasing the temperature to 650-950°C at a heating rate of 1-5°C / min and holding the temperature for 8-12 hours.
[0016] In some embodiments, the mass ratio of the intermediate to the single-walled carbon nanotubes is 300:1-3.
[0017] In some embodiments, the annealing temperature of step S2 is 300-500° C., and the annealing time is 3-5 hours.
[0018] In some embodiments, in step S3, the intermediate and the single-walled carbon nanotubes are mixed at a speed of 800-1200 rpm for 1-3 min, then at a speed of 1800-2200 rpm for 2-4 min, and finally at a speed of 3000-4000 rpm for 12-18 min.
[0019] In some embodiments, the sintering of the mixture in step S3 is a secondary sintering, and the specific steps include first keeping the mixture at 300-500° C. for 6-10 hours, and then keeping the mixture at 200-400° C. for 4-8 hours in an oxygen atmosphere.
[0020] In some embodiments, the lithium source includes at least one of lithium carbonate, lithium hydroxide, or lithium acetate.
[0021] In some embodiments, the aluminum source includes at least one of aluminum oxide, aluminum hydroxide, and aluminum carbonate.
[0022] In some embodiments, the zirconium source includes at least one of zirconium oxide and zirconium hydroxide.
[0023] In some embodiments, the niobium source includes at least one of niobium pentoxide and lithium niobate.
[0024] In some embodiments, the carbon nanotubes include single-walled carbon nanotubes.
[0025] In some embodiments, the molar ratio of lithium to transition metal elements in the lithium source is 0.95-1.2, and the transition metal elements include nickel, cobalt, aluminum, niobium and zirconium.
[0026] In some embodiments, based on the mass of the nickel-cobalt precursor, the doping amount of the aluminum element is 4000-20000 ppm, the doping amount of the zirconium element is 3000-5000 ppm, and the doping amount of the niobium element is 2000-5000 ppm.
[0027] In another aspect, the present invention provides a positive electrode material prepared by the above-mentioned method for preparing the positive electrode material.
[0028] The technical solution of the present invention has the following advantages:
[0029] 1. The present invention provides a method for preparing a positive electrode material, comprising the following steps: S1, mixing a nickel-cobalt precursor, a lithium source, an aluminum source, a zirconium source, and a niobium source, and sintering to obtain a sintered material; S2, immersing the sintered material in a lithium phosphate solution by an impregnation method, performing solid-liquid separation, and annealing to obtain an intermediate; S3, mixing the intermediate with single-walled carbon nanotubes to obtain a mixture, and sintering the mixture to obtain a positive electrode material. The present invention utilizes aluminum doping to reduce the nickel content in the positive electrode material, stabilize the structure, and reduce the impact on the capacity. By doping zirconium, the DC resistance of the material and the side reactions within the material are reduced, thereby increasing the lithium ion deintercalation rate. Furthermore, niobium doping is utilized to broaden the diffusion channel of lithium ions, reduce the activation energy of lithium ion migration, and improve the charge and discharge performance at high rates. At the same time, the strong bonding effect of niobium can improve the thermal stability of the material, reduce the oxygen evolution reaction caused by structural damage at high temperatures, thereby reducing the risk of thermal runaway and improving the safety of the battery. Lithium phosphate has ionic conductivity properties that can optimize the diffusion dynamics of lithium ions at the electrode-electrolyte interface. The present invention also uses lithium phosphate coating to improve the conductivity of lithium ions, optimize the interfacial lithium ion diffusion path, and reduce the charge transfer impedance. Furthermore, by depositing carbon nanotubes on the surface and utilizing the conductivity of carbon-based materials, a three-dimensional conductive network is constructed on the surface of high-nickel material particles and between particles, reducing electrode polarization and improving charge transfer efficiency. The high mechanical strength and flexibility of carbon nanotubes can also be used to buffer volume change stress, maintain the integrity of the electrode structure, and improve the stability of the material.
[0030] 2. The present invention provides a method for preparing a positive electrode material, wherein the particle size of the nickel-cobalt precursor is 2-6 μm, preferably 2-4 μm. The present invention utilizes a small-particle nickel-cobalt precursor, bulk-doped with zirconium, aluminum, and niobium to stabilize the structure and reduce lithium-nickel mixing. Simultaneously, an in-situ composite coating is used to form a continuous conductive-ion conductive composite layer. This internal and external combination enhances the material's conductivity, particularly by reducing lithium-ion diffusion resistance at high current densities, synergistically improving the material's rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the specific embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0032] Figure 1 This is a microscopic morphology of the positive electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0033] The following examples are provided for a better understanding of the present invention and are not intended to limit the best mode of implementation. They do not limit the content and scope of protection of the present invention. Any product identical or similar to the present invention obtained by anyone under the guidance of the present invention or by combining the features of the present invention with other prior arts shall fall within the scope of protection of the present invention.
[0034] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in this field can be used. If the manufacturer of the reagents or instruments is not specified, they are all commercially available conventional reagents.
[0035] Example 1
[0036] This embodiment provides a method for preparing a positive electrode material, and the specific steps and parameters are as follows:
[0037] (1) Weigh 500g of small Ni particles 0.90 Co 0.10 (OH)2 precursor, 235.697g lithium hydroxide, 6.949g Al(OH)3, 2.40g ZrO2 and 3.081g Nb2O5.
[0038] Among them, Ni 0.90 Co 0.10 The total amount of (OH)2 precursor is 10.65 mol / kg for small particles, and the specific surface area is 7.58m 2 / g, and the tap density is 1.90g / cm 3 The median particle size D50 is 2.86 μm. The purity of lithium hydroxide is 57.25%, and the purity of aluminum oxide, zirconium oxide and niobium pentoxide is above 99.9%.
[0039] The above raw materials were mixed evenly with a high-speed mixer, with the speed set at 1000 r / min for 2 min, then set at 2000 r / min for 3 min, and then set at 3500 r / min for 15 min, without setting any waiting time in between.
[0040] (2) The mixed powder in step S1 is heated to 500°C in a box furnace at a heating rate of 2°C / min, kept at 500°C for 4 hours, and then heated to 695°C at a heating rate of 2°C / min, kept at 695°C for 10 hours. The sintering atmosphere is oxygen with a flow rate of 2L / min, and the mixture is naturally cooled to room temperature. After crushing, a sintered material of lithium nickel cobalt aluminum oxide positive electrode material is obtained.
[0041] (3) Weigh 12.6 g of lithium hydroxide monohydrate, add it to 500 mL of deionized water, and stir magnetically (500 rpm, 30° C.) until it is completely dissolved to form a lithium hydroxide solution.
[0042] Use a pipette to measure 6.8 mL of 85 vol% phosphoric acid and add it dropwise to the lithium hydroxide solution. Monitor the pH in real time and maintain it at 9 to obtain a mixed solution. Add 500 mL of anhydrous ethanol to the mixture and sonicate (40 kHz, 30 min) until the solution becomes transparent and free of precipitate. Transfer the solution to a 1 L volumetric flask and dilute to 1 L with ethanol-water (1:1) to form a lithium phosphate solution. Store in a sealed glass bottle protected from light.
[0043] (4) Prepare the vacuum impregnation tank (vacuum degree ≤ 10 -3 Pa), constant temperature drying oven. Take 300g of the burnt material obtained in step (2), pour the lithium phosphate solution into the impregnation tank, and the liquid level should cover the burnt material particles by more than 2cm. Vacuum to 10 -3 Pa, maintain for 30 minutes to allow the solution to penetrate the particle pores. After returning to normal pressure, let it stand for 2 hours to ensure that the solution is fully adsorbed on the particle surface and pores. Centrifuge at 3000 rpm for 5 minutes to remove excess solution; then vacuum dry at 60°C for 12 hours to remove the solvent.
[0044] The material after removing the solvent was annealed at 400° C. for 4 h and then cooled to room temperature to obtain an intermediate.
[0045] (5) The intermediate obtained in step (4) and 0.15 g of single-walled carbon nanotubes were mixed at a rotation speed of 1000 r / min for 2 min, 2000 r / min for 3 min, and 3500 r / min for 15 min without setting a waiting time in between to obtain a mixture.
[0046] (6) Place the mixture in a box furnace for secondary firing at 400°C, keep warm for 8 hours, and cool naturally to obtain the secondary fired product of lithium nickel cobalt aluminum oxide positive electrode material. Then, sinter it in a box furnace with oxygen as the atmosphere, heat it to 300°C at a rate of 2°C / min, keep warm for 6 hours, cool naturally, and sieve it to obtain the positive electrode material.
[0047] See the microscopic morphology of the positive electrode material formed in this embodiment for Figure 1 .
[0048] Example 2
[0049] This embodiment provides a method for preparing a positive electrode material, and the specific steps and parameters are as follows:
[0050] (1) Weigh small Ni particles 0.90 Co 0.10(OH)2 precursor, lithium carbonate, aluminum oxide, zirconium hydroxide and niobium pentoxide, wherein the doping amount of aluminum element is 4000ppm, the doping amount of zirconium element is 5000ppm, the doping amount of niobium element is 2000ppm, and the ratio of the molar amount of lithium element to the sum of the molar amounts of nickel, cobalt, aluminum, zirconium and niobium elements is 1.2:1.
[0051] Among them, Ni 0.90 Co 0.10 The total amount of (OH)2 precursor is 10.20 mol / kg for small particles, and the specific surface area is 9.2m 2 / g, and the tap density is 2.8g / cm 3 The median particle size D50 is 2.1 μm. The purity of lithium carbonate is 56.81%, and the purity of aluminum oxide, zirconium hydroxide and niobium pentoxide is above 99.9%.
[0052] The above raw materials were mixed evenly with a high-speed mixer, with the speed set to 800 r / min for 3 min, then set to 2200 r / min for 2 min, and set to 3000 r / min for 18 min, without setting any waiting time in between.
[0053] (2) The mixed powder in step S1 is heated to 300°C at a heating rate of 1°C / min in a box furnace, kept at 400°C for 5 hours, and then heated to 650°C at a heating rate of 5°C / min, kept at 650°C for 12 hours. The sintering atmosphere is oxygen with a flow rate of 2L / min, and the mixture is naturally cooled to room temperature. After crushing, a sintered material of lithium nickel cobalt aluminum oxide positive electrode material is obtained.
[0054] (3) Weigh 12.6 g of lithium hydroxide monohydrate, add it to 500 mL of deionized water, and stir magnetically (500 rpm, 30° C.) until it is completely dissolved to form a lithium hydroxide solution.
[0055] Use a pipette to measure 6.8 mL of 85 vol% phosphoric acid and add it dropwise to the lithium hydroxide solution. Monitor the pH in real time and maintain it at 8 to obtain a mixed solution. Add 500 mL of anhydrous ethanol to the mixture and sonicate (40 kHz, 30 min) until the solution becomes transparent and free of precipitate. Transfer the solution to a 1 L volumetric flask and dilute to 1 L with ethanol-water (1:1) to form a lithium phosphate solution. Store in a sealed glass bottle protected from light.
[0056] (4) Prepare the vacuum impregnation tank (vacuum degree ≤ 10 -3 Pa), constant temperature drying oven. Take 300g of the burnt material obtained in step (2), pour the lithium phosphate solution into the impregnation tank, and the liquid level should cover the burnt material particles by more than 2cm. Vacuum to 10 -3Pa, maintain for 20 minutes to allow the solution to penetrate the particle pores. After returning to normal pressure, let it stand for 3 hours to ensure that the solution is fully adsorbed on the particle surface and pores. Centrifuge at 3000 rpm for 5 minutes to remove excess solution; then vacuum dry at 60°C for 12 hours to remove the solvent.
[0057] The material after removing the solvent was annealed at 300° C. for 5 h and then cooled to room temperature to obtain an intermediate.
[0058] (5) The intermediate obtained in step (4) and 0.1 g of single-walled carbon nanotubes were mixed at a speed of 1200 r / min for 1 min, 1800 r / min for 4 min, and 4000 r / min for 12 min without setting a waiting time in between to obtain a mixture.
[0059] (6) Place the mixture in a box furnace for secondary firing at 300°C, keep warm for 10 hours, and cool naturally to obtain the secondary fired product of lithium nickel cobalt aluminum oxide positive electrode material. Then, sinter it in a box furnace with oxygen as the atmosphere, heat it to 200°C at a rate of 2°C / min, keep warm for 8 hours, cool naturally, and sieve it to obtain the positive electrode material.
[0060] Example 3
[0061] This embodiment provides a method for preparing a positive electrode material, and the specific steps and parameters are as follows:
[0062] (1) Weigh small Ni particles 0.90 Co 0.10 (OH)2 precursor, lithium acetate, aluminum carbonate, zirconium oxide and lithium niobate, wherein the doping amount of aluminum element is 20000ppm, the doping amount of zirconium element is 3000ppm, the doping amount of niobium element is 5000ppm, and the ratio of the molar amount of lithium element to the sum of the molar amounts of nickel, cobalt, aluminum, zirconium and niobium elements is 0.9:1.
[0063] Among them, Ni 0.90 Co 0.10 The total amount of (OH)2 precursor is 10.28 mol / kg for small particles, and the specific surface area is 6.3m 2 / g, and the tap density is 1.25g / cm 3 The median particle size D50 is 3.9 μm. The purity of lithium acetate is 57.25%, and the purity of aluminum carbonate, zirconium oxide and lithium niobate is above 99.9%.
[0064] The above raw materials were mixed evenly with a high-speed mixer, with the speed set at 1200 r / min for 1 min, then set at 1800 r / min for 4 min, and then set at 4000 r / min for 12 min, without setting any waiting time in between.
[0065] (2) The mixed powder in step S1 is heated to 500°C in a box furnace at a heating rate of 5°C / min, kept at 600°C for 3 hours, and then heated to 950°C at a heating rate of 1°C / min, kept at 950°C for 8 hours. The sintering atmosphere is oxygen with a flow rate of 2L / min, and the mixture is naturally cooled to room temperature. After crushing, a sintered material of lithium nickel cobalt aluminum oxide positive electrode material is obtained.
[0066] (3) Weigh 12.6 g of lithium hydroxide monohydrate, add it to 500 mL of deionized water, and stir magnetically (500 rpm, 30° C.) until it is completely dissolved to form a lithium hydroxide solution.
[0067] Use a pipette to measure 6.8 mL of 85 vol% phosphoric acid and add it dropwise to the lithium hydroxide solution. Monitor the pH in real time and maintain it at 8 to obtain a mixed solution. Add 500 mL of anhydrous ethanol to the mixture and sonicate (40 kHz, 30 min) until the solution becomes transparent and free of precipitate. Transfer the solution to a 1 L volumetric flask and dilute to 1 L with ethanol-water (1:1) to form a lithium phosphate solution. Store in a sealed glass bottle protected from light.
[0068] (4) Prepare the vacuum impregnation tank (vacuum degree ≤ 10 -3 Pa), constant temperature drying oven. Take 300g of the burnt material obtained in step (2), pour the lithium phosphate solution into the impregnation tank, and the liquid level should cover the burnt material particles by more than 2cm. Vacuum to 10 -3 Pa, maintain for 40 minutes to allow the solution to penetrate the particle pores. After returning to normal pressure, let it stand for 1 hour to ensure that the solution is fully adsorbed on the particle surface and pores. Centrifuge at 3000 rpm for 5 minutes to remove excess solution; then vacuum dry at 60°C for 12 hours to remove the solvent.
[0069] The material after removing the solvent was annealed at 500° C. for 3 h and then cooled to room temperature to obtain an intermediate.
[0070] (5) The intermediate obtained in step (4) and 0.3 g of single-walled carbon nanotubes were mixed at a rotation speed of 1200 r / min for 1 min, 2200 r / min for 2 min, and 3000 r / min for 18 min without setting a waiting time in between to obtain a mixture.
[0071] (6) Place the mixture in a box furnace for secondary firing at 500°C and hold for 6 hours to obtain a secondary fired product of the lithium nickel cobalt aluminum oxide positive electrode material. The mixture is then secondary fired in a box furnace with an oxygen atmosphere at a heating rate of 2°C / min to 400°C, held for 4 hours, and cooled naturally before sieving to obtain the positive electrode material.
[0072] Example 4
[0073] This embodiment provides a method for preparing a positive electrode material. The specific steps and parameters are the same as those in Example 1, except that the concentration of lithium phosphate in the lithium phosphate solution in step (3) is 0.05M.
[0074] Example 5
[0075] This embodiment provides a method for preparing a positive electrode material. The specific steps and parameters are the same as those in Example 1, except that the concentration of lithium phosphate in the lithium phosphate solution in step (3) is 0.2M.
[0076] Example 6
[0077] This embodiment provides a method for preparing a positive electrode material. The specific steps and parameters are the same as those in Example 1, except that in step (1), Ni 0.90 Co 0.10 The total amount of (OH)2 precursor is 10.93 mol / kg for small particles, and the specific surface area is 5.28m 2 / g, and the tap density is 1.62g / cm 3 , the median particle size D50 is 6 μm.
[0078] Example 7
[0079] This embodiment provides a method for preparing a positive electrode material. The specific steps and parameters are the same as those in Example 1, except that, in step (4), 300 g of the burnt material obtained in step (2) is taken, and the lithium phosphate solution is poured into an impregnation tank so that the liquid level covers the burnt material particles by more than 2 cm. The mixture is immersed for 2.5 hours, centrifuged at 3000 rpm for 5 minutes, and excess solution is removed; and then vacuum dried at 60°C for 12 hours to remove the solvent.
[0080] Example 8
[0081] This embodiment provides a method for preparing a positive electrode material. The specific steps and parameters are the same as those in Example 1. The difference is that in step (4), a vacuum impregnation tank (vacuum degree ≤ 10 -3 Pa), constant temperature drying oven. Take 300g of the burnt material obtained in step (2), pour the lithium phosphate solution into the impregnation tank, and the liquid level should cover the burnt material particles by more than 2cm. Vacuum to 10 -3 Pa, and maintain for 30 minutes to allow the solution to penetrate into the pores of the particles. Centrifuge at 3000 rpm for 5 minutes to remove excess solution, and then vacuum dry at 60°C for 12 hours to remove the solvent.
[0082] Comparative Example 1
[0083] This comparative example provides a method for preparing a positive electrode material. The specific steps and parameters are the same as those in Example 1, except that step (1) does not contain ZrO2. That is, 500g of small particles of Ni0.90 Co 0.10 (OH)2 precursor, 235.697g lithium hydroxide, 6.949g Al(OH)3 and 3.081g Nb2O5.
[0084] Comparative Example 2
[0085] This comparative example provides a method for preparing a positive electrode material. The specific steps and parameters are the same as those in Example 1, except that step (1) does not contain Nb2O5. That is, 500g of small particles of Ni 0.90 Co 0.10 (OH)2 precursor, 235.697g lithium hydroxide, 6.949g Al(OH)3 and 2.40g ZrO2.
[0086] Comparative Example 3
[0087] This comparative example provides a method for preparing a positive electrode material. The specific steps and parameters are the same as those in Example 1, except that steps (3) and (4) are not included, and the lithium nickel cobalt aluminum oxide positive electrode material in step (2) is used as the intermediate of step (5) and is mixed and sintered with single-arm carbon nanotubes.
[0088] Comparative Example 4
[0089] This comparative example provides a method for preparing a positive electrode material. The specific steps and parameters are the same as those in Example 1, except that step (5) is not included, that is, step (6) is performed on the intermediate.
[0090] Comparative Example 5
[0091] This comparative example provides a method for preparing a positive electrode material. The specific steps and parameters are the same as those in Example 1, except that steps (3) to (5) are not included, that is, step (6) is performed on the sintered material of the lithium nickel cobalt aluminum oxide positive electrode material in step (2).
[0092] Comparative Example 6
[0093] This comparative example provides a method for preparing a positive electrode material. The specific steps and parameters are the same as those in Example 1, except that an equimolar amount of ferric hydroxide is used to replace the lithium hydroxide monohydrate in step (3).
[0094] Comparative Example 7
[0095] This comparative example provides a method for preparing a positive electrode material. The specific steps and parameters are the same as those in Example 1, except that an equimolar amount of cobalt hydroxide is used to replace the lithium hydroxide monohydrate in step (3).
[0096] Comparative Example 8
[0097] This comparative example provides a method for preparing a positive electrode material. The specific steps and parameters are the same as those in Example 1, except that steps (3)-(4) are not set, and the following steps are used instead of step (5) in Example 1, that is, 300 g of the sintered material obtained in step (2), 11.6 g of lithium phosphate and 0.15 g of single-arm carbon nanotubes are taken, and the speed is set to 1000 r / min for mixing for 2 min, 2000 r / min for mixing for 3 min, and 3500 r / min for mixing for 15 min, without setting a waiting time in between, to obtain a mixed material.
[0098] The remaining steps are the same as those in Example 1.
[0099] Experimental example
[0100] The positive electrode materials prepared in Examples 1-8 and Comparative Examples 1-8 were subjected to electrical performance tests according to the following method: 95 (positive electrode material): 3 (polyvinylidene fluoride): 2 (conductive carbon black) mass ratio was used for homogenization, and then aluminum foil was spread flat on a coating machine for coating (surface density 13.3-13.5 mg / cm 2 , compacted density 3.3-3.5mg / cm 2 ) and dried in an 80°C forced air drying oven for 3 hours; then, the cells were punched, weighed, and the electrodes baked to form button-type batteries. Electrical performance testing was conducted using a blue-electric test system within a cut-off voltage range of 2.5V-4.25V, with the following charge and discharge cycles: first cycle (0.2C / 0.2C), second to fourth cycles (0.2C / 0.5C), fifth to seventh cycles (0.2C / 1C), eighth to tenth cycles (1C / 3C), and eleventh to thirteenth cycles (1C / 5C). The test results are shown in Table 1.
[0101] Table 1 Test performance results
[0102]
[0103]
[0104] According to Table 1, compared with Comparative Example 1 without zirconium doping, Comparative Example 2 without niobium doping, Comparative Example 3 without lithium phosphate coating, Comparative Example 4 without carbon nanotube coating, Comparative Example 5 without lithium phosphate and carbon nanotube coating, Comparative Example 6 coated with iron phosphate, Comparative Example 7 coated with cobalt phosphate, and Comparative Example 8 coated with lithium phosphate using a solid phase method, the preparation method of the positive electrode material provided in the embodiment of the present invention can effectively improve the discharge capacity of the material.
[0105] Obviously, the above embodiments are merely examples for clarity of explanation and are not intended to limit the implementation methods. Those skilled in the art will readily appreciate that other variations or modifications based on the above descriptions are possible. It is not necessary and impossible to enumerate all implementation methods here. Obvious variations or modifications arising therefrom remain within the scope of protection of the present invention.
Claims
1. A method for preparing a positive electrode material, characterized in that: The following steps are included: S1, mixing a nickel-cobalt precursor, a lithium source, an aluminum source, a zirconium source, and a niobium source, and sintering to obtain a sintered material; S2, immersing a sintered material in a lithium phosphate solution by an immersion method, separating the solid and the liquid, and annealing to obtain an intermediate; S3, mixing the intermediate and the carbon nanotubes to obtain a mixture, and sintering the mixture to obtain a positive electrode material.
2. The method for preparing the positive electrode material according to claim 1, wherein: The step of immersing the sinter in the lithium phosphate solution in step S2 comprises immersing the sinter in the lithium phosphate solution under vacuum conditions for 20-40 minutes and then under normal pressure conditions for 1-3 hours; and / or, The solid-liquid separation step in step S2 includes centrifugation and drying. The centrifugal speed is 2000-4000 rpm, the centrifugal time is 4-6 minutes, the drying temperature is 50-70°C, the drying time is 10-14 hours, and the drying condition is vacuum.
3. The method for preparing the positive electrode material according to claim 1, wherein: The preparation method of the lithium phosphate solution comprises the following steps: in the presence of an alcohol solvent, adding phosphoric acid dropwise to a lithium hydroxide solution, and controlling the pH value of the reaction system to be 8-9; and / or, The concentration of lithium phosphate in the lithium phosphate solution is 0.05-0.2M, preferably 0.1M.
4. The method for preparing the positive electrode material according to claim 1, wherein: The particle size of the nickel-cobalt precursor is 2-6 μm, preferably 2-4 μm; and / or, The specific surface area of the nickel-cobalt precursor is 5-10m 2 / g, tap density is 1-3g / cm 3 .
5. The method for preparing the positive electrode material according to claim 4, wherein: In step S1, the step of mixing the nickel-cobalt precursor, lithium source, aluminum source, zirconium source and niobium source includes mixing the intermediate and single-walled carbon nanotubes at a speed of 800-1200 rpm for 1-3 minutes, then mixing at a speed of 1800-2200 rpm for 2-4 minutes, and finally mixing at a speed of 3000-4000 rpm for 12-18 minutes; and / or, The sintering conditions in step S1 include increasing the temperature to 400-600°C at a heating rate of 1-5°C / min and holding for 3-5 hours in air or oxygen atmosphere, and then increasing the temperature to 650-950°C at a heating rate of 1-5°C / min and holding for 8-12 hours.
6. The method for preparing the positive electrode material according to claim 5, wherein: The mass ratio of the intermediate to the single-walled carbon nanotube is 300:1-3; and / or, The annealing temperature of step S2 is 300-500° C., and the annealing time is 3-5 hours.
7. The method for preparing the positive electrode material according to claim 6, wherein: In step S3, the intermediate and the single-walled carbon nanotubes are mixed at a speed of 800-1200 rpm for 1-3 min, then at a speed of 1800-2200 rpm for 2-4 min, and finally at a speed of 3000-4000 rpm for 12-18 min; and / or, The sintering of the mixed material in step S3 is secondary sintering, and the specific steps include first keeping the mixed material at 300-500° C. for 6-10 hours, and then keeping it at 200-400° C. for 4-8 hours in an oxygen atmosphere.
8. The method for preparing the positive electrode material according to claim 1, wherein: The lithium source includes at least one of lithium carbonate, lithium hydroxide or lithium acetate; and / or, The aluminum source includes at least one of aluminum oxide, aluminum hydroxide, and aluminum carbonate; and / or The zirconium source includes at least one of zirconium oxide and zirconium hydroxide; and / or, The niobium source includes at least one of niobium pentoxide and lithium niobate; and / or, The carbon nanotubes include single-arm carbon nanotubes.
9. The method for preparing the positive electrode material according to claim 1, wherein: Based on the mass of the nickel-cobalt precursor, the doping amount of the aluminum element is 4000-20000 ppm, the doping amount of the zirconium element is 3000-5000 ppm, and the doping amount of the niobium element is 2000-5000 ppm.
10. A positive electrode material, characterized in that The positive electrode material is prepared by the preparation method of any one of claims 1 to 9.
Citation Information
Patent Citations
Three-dimensional carbon nanotube-modified spinel lithium nickel manganese oxide material and preparation method and application thereof
CN105226267A
Preparation method of niobium-doped lithium nickel cobalt aluminate cathode material
CN111653765A
Nano lithium phosphate coated high-nickel ternary positive electrode material and preparation method thereof
CN114524469A
Surface modification method of positive electrode
CN119673972A